Factors affecting job satisfaction at Hyundai – Sime Darby Motors Sdn. Bhd. / Nora Hazwani Azmi - Azmi, Nora Hazwani (Faculty of Business and Management, 2018)
This study is aimed to test the relationship of employees’ empowerment, employees’ training and teamwork on job satisfaction in a private sector organization, Hyundai – Sime Darby Motors (HSDM) Sdn. Bhd. at Shah Alam. This relationship was examined based on independent variables which are employees’ empowerment, employees’ training and teamwork. This study used quantitative method whereby set of questionnaires are used to collect the data. There were 66 respondents. The data analyses in this study were analysed using IBM SPSS statistics software. Descriptive statistics were used to measure relationship between employees’ empowerment, employees’ training, teamwork and job satisfaction. Meanwhile, testing of means analysis, Pearson Coefficient and multiple regression analysis were performed to examine the relationship between employees’ empowerment, employees’ training, teamwork and job satisfaction. Results indicate that there is a strong significant relationship between employees’ empowerment, employees’ training, teamwork and job satisfaction. The discussions of study implications and future research will be explained at the end of this study.